ACVIM consensus statement guidelines for the classification, diagnosis, and management of cardiomyopathies in cats. (3rd April 2020) - Luis Fuentes, Virginia; Abbott, Jonathan; Chetboul, Valérie; Côté, Etienne; Fox, Philip R.; Häggström, Jens; Kittleson, Mark D.; Schober, Karsten; Stern, Joshua A.
Abstract: Cardiomyopathies are a heterogeneous group of myocardial disorders of mostly unknown etiology, and they occur commonly in cats. In some cats, they are well‐tolerated and are associated with normal life expectancy, but in other cats they can result in congestive heart failure, arterial thromboembolism or sudden death. Cardiomyopathy classification in cats can be challenging, and in this consensus statement we outline a classification system based on cardiac structure and function (phenotype). We also introduce a staging system for cardiomyopathy that includes subdivision of cats with subclinical cardiomyopathy into those at low risk of life‐threatening complications and those at higher risk. Based on the available literature, we offer recommendations for the approach to diagnosis and staging of cardiomyopathies, as well as for management at each stage.